Morphology control in polysulfone-modified epoxy resins by demixing behavior - Giannotti, Marina Inés (2003)
Polysulfone (PSu) was used as a modifier of epoxy/aromatic diamine formulations. Two epoxy monomers, based on diglycidyl ether of bisphenol A (DGEBA), were used. The cure agent was 4,4′-diaminodiphenylsulfone. PSu was miscible with DGEBA, as shown by the existence of a single glass-transition temperature within the whole composition range. The effect of PSu addition on the cure kinetics was investigated. The reaction rate of the epoxy-amine species was slightly lower in the presence of PSu. The morphology was analyzed by optical and scanning electron microscopy. A range of microstructures were obtained by control over the cure temperature, the amount of PSu incorporated, and the molecular weights of the epoxy resins. The variations in the morphology resulted from the different stages of demixing, which were arrested because of the different developments of the viscosity of the system. © 2003 Wiley Periodicals, Inc.